Creation of Ionically Crosslinked Tri-Layered Chitosan Membranes to Simulate Different Human Skin Properties - Rocío Guerle-Cavero; Blanca Lleal-Fontàs; Albert Balfagón-Costa (Materials, 2021)
In 2023, new legislation will ban the use of animals in the cosmetic industry worldwide. This fact, together with ethical considerations concerning the use of animals or humans in scientific research, highlights the need to propose new alternatives for replacing their use. The aim of this study is to create a tri-layered chitosan membrane ionically crosslinked with sodium tripolyphosphate (TPP) in order to simulate the number of layers in human skin. The current article highlights the creation of a membrane where pores were induced by a novel method. Swelling index, pore creation, and mechanical property measurements revealed that the swelling index of chitosan membranes decreased and, their pore formation and elasticity increased with an increase in the Deacetylation Grade (DDA). Additionally, the results demonstrate that chitosan’s origin can influence the elastic modulus value and reproducibility, with higher values being obtained with seashell than snow crab or shrimp shells. Furthermore, the data show that the addition of each layer, until reaching three layers, increases the elastic modulus. Moreover, if layers are crosslinked, the elastic modulus increases to a much greater extent. The characterization of three kinds of chitosan membranes was performed to find the most suitable material for studying different human skin properties.